Alchool use, adherence to antiretroviral treatment, immunological and virological parameters, surviral and religiosity/spirituality among persons living with HIV - over 4 Years (Research, Society and Development, 2022)
Religiosity and spirituality have been associated with healthier behaviors and less depression in people living with HIV (PLWH) who attend monthly religious services. However, studies evaluating hospitalized patients and follow-up adherence to antiretroviral therapy (ART) are lacking. The aim of this study was to examine the influence of religiosity/spirituality on alcohol and substance use, depression, ART, immunological and virological parameters, hospitalizations, hospital costs, and survival among 84 PLWH hospitalized. Cohort with a follow-up of 4 years. The findings of this study show that patients with less use of alcoholic beverages are more likely to practice individual religious activities. Higher CD4 cell counts, lower viral load counts during hospitalization, better adherence to ART, and lower mortality over 4 years are associated high intrinsic religiosity in PLWH. Practice individual religious activities are associated with less use of alcoholic beverages, and spirituality with better adherence to ART, and lower mortality. In view of the benefits shown in this study and the literature, spiritual complementary approaches should be encouraged in hospitals and health institutions as an integrative approach to health.